Isolated Propriospinal Myoclonus as a Presentation of Cervical Myelopathy. (26th November 2018) - Marrero-González, Paula; Pascual-Sedano, Berta; Martínez-Domeño, Alejandro; Díaz-Polo, L. Estefanía; Granell, Esther; Rodríguez, Rodrigo; Gironell, Alexandre; Guisado-Alonso, Daniel
Background: Propriospinal myoclonus is an infrequent type of hyperkinetic movement that can be commonly idiopathic but also may occur after spinal cord lesions. Phenomenology Shown: We describe an 8-year-old female showing repetitive flexor and extensor arrhythmic brief jerks of the trunk, compatible with propriospinal myoclonus secondary to cervical myelopathy. Educational Value: Isolated propriospinal myoclonus may be the clinical sign that leads to the diagnosis of incipient myelopathy.